Mediating role of e-learning quality between organizational learning and e-learning among corporate e-learners in a Malaysian company - Balakrishnan, Sharmini Marilyn (2021)
Ideally, poor e-learning use should not be an issue among corporate e-learners because e-learning enables organizations to effectively integrate learning into their employees’ day-to-day work. However, many companies have found that their e-learning systems are often underused. This indicates that employees are not getting the requisite training, leading to poor performance and productivity, and high turnover. Unfortunately, previous studies have not studied e-learning use in the context of organizational learning and e-learning quality (Yakubu & Dasuki, 2018; Liu et al., 2012), despite their influence on e-learning use (Al-Fraihat et al., 2020; Wang, 2018). Furthermore, there is limited corporate e-learning research in Malaysia as the focus has been on the education sector. Therefore, the purpose of this study was to examine the relationships of e-learning quality, organizational learning and e-learning use. A descriptive correlational research design with a quantitative survey method was used in this research. The questionnaire was adapted from the E-learning Success System (ELSS) and the Strategic Learning Assessment Map (SLAM) instruments. Data from 261 employees of an oil and gas company in Sarawak, Malaysia was analyzed through IBM SPSS 23.0 and AMOS 23.0. The findings show that males, the non-technical departments, management and senior e-learners had higher levels for e-learning quality, organizational learning and e-learning use. Also, e-learning quality fully mediated the relationship between organizational learning and e-learning use (β = 0.65, t = 1.98, p < 0.05) with a medium effect size and the mediation model explained 51.2% of the variation on e-learning use. The main barrier to e-learning use was time constraints and improving e-learning content was the most popular suggestion to increase e-learning use. In conclusion, this study gave useful insights on the relationships between organizational learning, e-learning quality and e-learning use. It proposes a parsimonious higher-order structural equation model to study corporate e-learning more effectively and presents individual-level perceptions on e-learning for researchers and practitioners.